2008
DOI: 10.1073/pnas.0711119105
|View full text |Cite
|
Sign up to set email alerts
|

Osteocalcin differentially regulates β cell and adipocyte gene expression and affects the development of metabolic diseases in wild-type mice

Abstract: The osteoblast-specific secreted molecule osteocalcin behaves as a hormone regulating glucose metabolism and fat mass in two mutant mouse strains. Here, we ask two questions: is the action of osteocalcin on ␤ cells and adipocytes elicited by the same concentrations of the molecule, and more importantly, does osteocalcin regulate energy metabolism in WT mice? Cell-based assays using isolated pancreatic islets, a ␤ cell line, and primary adipocytes showed that picomolar amounts of osteocalcin are sufficient to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

57
798
9
30

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 856 publications
(894 citation statements)
references
References 21 publications
57
798
9
30
Order By: Relevance
“…Polymorphisms may not be able to reflect the status of posttranslational modification (g-carboxylation) that appears to be the mechanism by which OC bioactivity is regulated. (16,18) In corroboration of other studies, (41,42) OC levels (total and carboxylated) were significantly correlated with bone mass, and women with high OC levels had lowest TB BMD. Serum OC also predicted fracture risk independent of weight and bone mass.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Polymorphisms may not be able to reflect the status of posttranslational modification (g-carboxylation) that appears to be the mechanism by which OC bioactivity is regulated. (16,18) In corroboration of other studies, (41,42) OC levels (total and carboxylated) were significantly correlated with bone mass, and women with high OC levels had lowest TB BMD. Serum OC also predicted fracture risk independent of weight and bone mass.…”
Section: Discussionsupporting
confidence: 86%
“…(16,17) Another study done in wild-type mice also observed the importance of osteocalcin in the regulation of glucose metabolism and fat mass. (18) At its simplest level, this relationship offers a plausible link between the established inverse relationship between body size, osteoporosis, and fracture risk.…”
Section: Introductionmentioning
confidence: 99%
“…It is this undercarboxylated form of osteocalcin that appears to function as a hormone and alter pancreatic b-cell proliferation, insulin expression, insulin secretion, insulin sensitivity, and energy PERSPECTIVE J JBMR expenditure. (5,6) In accordance with this concept, treatment of wild-type mice with warfarin decreased blood glucose levels. (7) In an unexpected turn of events, the osteoblast was found to express the Esp gene, which encodes a protein tyrosine phosphatase that hampers glucose metabolism by inhibiting osteocalcin endocrine functions.…”
Section: Introductionmentioning
confidence: 75%
“…Now it is well-accepted that the skeleton is an endocrine organ that, through the secreted molecule osteocalcin (Bgla), favors insulin secretion by insulin-producing b cells and insulin sensitivity in liver, muscle, and adipocytes (Ferron et al 2008;Fukumoto and Martin 2009;Hinoi et al 2008;Lee et al 2007;Lee 2010;Lieben et al 2009;Schwetz et al 2012). The protein osteocalcin is produced by osteoblasts and odontoblasts and has been known as a marker of bone turnover (Brown et al 1984;Ducy 2011).…”
Section: Discussionmentioning
confidence: 99%